Analysis of the E-J Curve of HTS Tapes Under DC and AC Magnetic Fields at 77 K - Shigue, Carlos Yujiro; da Cruz, Tatiane Tobias; Lamas, Jerika Suely; Baldan, Carlos Alberto [UNESP]; Ruppert Filho, Ernesto (Institute of Electrical and Electronics Engineers (IEEE), 2009)
The evaluation of the electrical characteristics of technical HTS tapes are of the key importance in determining the design and operational features of superconducting power apparatuses as well as to understand the external factors which affect the superconducting performance. In this work we report the systematic measurements of the electric field versus current density, E-J relation of short samples for three commercial HTS tapes (BSCCO-2223 tapes, with and without steel reinforcement, and YBCO-coated conductor) at 77 K. In order to get sensitive and noiseless voltage signals the measurements were carried out with DC transport current and subjecting the broad surface tape to DC (0-300 mT) and AC (0-62 mT, 60 Hz) magnetic fields. The voltage is measured by a sensitive nanovoltmeter and the applied magnetic field is monitored by a Hall sensor placed on the tape broad surface. The comparison between the results obtained from the three tapes was done by fitting a power-law equation for currents in the vicinity of the critical current. For the current regime below the critical one a linear correlation of the electric field against the current density is observed. The BSCCO samples presented the same behavior, i.e., a decreasing of n-index with the increasing DC and AC magnetic field strength. Under AC field the decreasing slope of n-index is steeper as compared to DC field. The n-index curve for the YBCO tape showed similar behavior for AC field, however under DC field in the 0-390 mT range exhibited a slight decreasing of the n-index.
Keywords: AC losses; critical current; HTS tapes; power-law relation